Evaluation of Zinc solubilization potential by different strains of Fluorescent Pseudomonads - Azadeh Bapiri; Ahmad Asgharzadeh; Hesam Mujallali; Kazem Khavazi; Ebrahim Pazira (Journal of Applied Sciences and Environmental Management)
Zinc solubilizing ability of Pseudomonas fluorescent was evaluated using zinc oxide, zinc carbonate and zinc sulphide in both plate and broth media assays. Forty bacterial strains and 0.1% of each chemical source in six replications were used. Colony and halo diameters were measured after incubating the plates for 48h in incubator. Zn solubilizing ability of 40 mentioned strains in three replications was studied with ZnO and ZnCO3 solutions in broth assay. The soluble zinc and pH were measured after five days. The results showed, only 8 of 40 strains could form clearing zone in plate assay. Halo diameter, ratio of the halo diameter to the colony diameter and area respectively for zinc oxide and zinc carbonate were as following, respectively: 0.60-1.32 cm, 1.20-2.64 and 0.95-2.60 cm2, 0.13-1.70 cm, 0.27-2.99 and 0.31-4.10 cm2. There were no halos observed in zinc sulphide. The concentration of soluble Zn for ZnO was 28-625 mg/l and pH was shifted from 7.0-7.2 to 3.90-6.50 and for ZnCO3 was 247-753 mg/l and pH was shifted from 7.0-7.2 to 3.5-6.3 after 5 days of inoculation in 28ºC.